ANALISIS MINAT BELAJAR SISWA TERHADAP PEMBELAJARAN MATEMATIKA PADA SISWA SMA DI KABUPATEN BANDUNG BARAT - Astri Yuliani Nurhafifah; Mayasari Mayasari (Journal on Education, 2019)
The purpose of this research is to know student’s learning interest, in mathematics learning of high school students in West Bandung Regency. The method used in this research is survey method. The research technique was carried out by distributing questionnaires, which were then analyzed descriptively. The questionnaire consisted of thirthy questions with four alternative answers, which is "strongly agree" (SS), "agree" (S), "Disagree" (TS), and strongly disagree "(STS). The population in this research is all of the high school students in West Bandung Regency, and the sample was thirty students in elevent grade from one of several hight school in West Bandung Regency. The results of this research state that, students who like to mathematics learning are only 33% with low categories, low. The biggest percentage of student interest is 87% with categories, very high. And the same percentage for student attention and involvement is 54% with categories, medium. This shows that, students have interest, attention and involvement, even thought they do not like mathematics learning.